2005
DOI: 10.1152/ajpgi.00369.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization and expression of kinin B1R and B2R receptors in human inflammatory bowel disease

Abstract: Bradykinin is a mediator of inflammation, responsible for pain, vasodilation, and capillary permeability. Bradykinin receptor 1 (B1R) and bradykinin receptor 2 (B2R) are G protein-coupled receptors that mediate kinin effects. The latter is constitutive and rapidly desensitized; the former is induced by inflammatory cytokines and resistant to densensitization. The distribution of bradykinin receptors in human intestinal tissue was studied in patients with inflammatory bowel disease (IBD), namely ulcerative coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…BK-receptor expression in inflammatory bowel disease, namely, ulcerative colitis and Crohn's disease, may be altered in intestinal inflammation. Increased B1R gene and protein expression in active inflammatory bowel disease provides a structural basis for the important role of kinins in chronic inflammation (303).…”
Section: Pain and Neurological Applicationsmentioning
confidence: 99%
“…BK-receptor expression in inflammatory bowel disease, namely, ulcerative colitis and Crohn's disease, may be altered in intestinal inflammation. Increased B1R gene and protein expression in active inflammatory bowel disease provides a structural basis for the important role of kinins in chronic inflammation (303).…”
Section: Pain and Neurological Applicationsmentioning
confidence: 99%
“…The kallikrein-kinin system consists of circulating kininogens, the proteolytic enzymes factor XII and prekallikrein, kinins, and two G protein-coupled receptors termed kinin B 1 and bradykinin B 2 receptors, which mediate the biological effects of kinins (1,24). Both B 1 and B 2 receptors have been immunolocalized in the epithelial cells of affected human intestinal tissue (38). A kinin B 1 antagonist attenuates the inflammatory changes in the experimental colitis model (17).…”
mentioning
confidence: 99%
“…In dextran sulfate (DDS) -induced colitis model in mice a selective B2R antagonist suppressed shortening of the large intestine (Arai et al, 1999), which was in agreement with future results indicated that intestinal contraction was regulated by B2R (Hara et al, 2007), however demonstrated only limited effect in intestinal inflammatory lesions. Later in human studies we demonstrated the increase in the ratio of B1R to B2R gene expression in relation to the degree of intestinal inflammation, and visualized both B1R and B2R in normal as well as inflammatory human colon and ileum (Stadnicki et al, 2005). B2R protein was normally present in the apices of enterocytes in the basal area and intracellularly in inflammatory tissue.…”
Section: Kinins and Kinin Receptors In Ibdmentioning
confidence: 88%